2008
DOI: 10.1093/hmg/ddn303
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA background modulates the assembly kinetics of OXPHOS complexes in a cellular model of mitochondrial disease

Abstract: Leber's hereditary optic neuropathy (LHON), the most frequent mitochondrial disorder, is mostly due to three mitochondrial DNA (mtDNA) mutations in respiratory chain complex I subunit genes: 3460/ND1, 11778/ND4 and 14484/ND6. Despite considerable clinical evidences, a genetic modifying role of the mtDNA haplogroup background in the clinical expression of LHON remains experimentally unproven. We investigated the effect of mtDNA haplogroups on the assembly of oxidative phosphorylation (OXPHOS) complexes in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 36 publications
9
103
0
Order By: Relevance
“…3,23,24 Recent studies have identified an increasing number of cancers associated with various mtDNA haplogroups within the human population. Tanaka's group analyzed a population with 1,503 autopsied cases and identified genotypes for 149 polymorphisms within the coding region of the mitochondrial genome.…”
Section: Inherited Mtdna Mutations and Predisposition To Cancermentioning
confidence: 99%
“…3,23,24 Recent studies have identified an increasing number of cancers associated with various mtDNA haplogroups within the human population. Tanaka's group analyzed a population with 1,503 autopsied cases and identified genotypes for 149 polymorphisms within the coding region of the mitochondrial genome.…”
Section: Inherited Mtdna Mutations and Predisposition To Cancermentioning
confidence: 99%
“…Our group analyzed the effect of the most common LHON mutations that lead to complex I deficiency on the assembly of the native mitochondrial RC complexes, and also checked whether distinct mitochondrial genetic backgrounds differentially affected this process (Pello et al, 2008). This work demonstrated that the same mutation could produce different alterations not only in the assembly kinetics of complex I, but also in complexes III and IV in the mutant cells, which depended on the analyzed mitochondrial haplogroup.…”
Section: Role Of the Mtdna Genetic Background On The Rc Dysfunction Amentioning
confidence: 99%
“…The question of whether mtDNA haplogroups are functionally relevant has also been raised, and one recent cybrid study did find differences in mitochondrial respiratory capacity in cells containing haplogroup H versus haplogroup Uk (40). Other cybrid studies have similarly reported that common mtDNA polymorphisms may influence mitochondrial function (54,99).…”
Section: Are Specific Mtdna Signatures Typical Of Pd?mentioning
confidence: 99%
“…It increasingly appears these polymorphisms may subtly influence mitochondrial function (40,54,99). This may apply to even extremely common synonymous mtDNA polymorphisms that do not cause amino acid substitutions (70).…”
Section: Are Specific Mtdna Signatures Typical Of Pd?mentioning
confidence: 99%